Effects of controlled atmosphere temperature treatment (CATT) for Phytonemus pallidus management on plant survival, yield and growth of strawberry transplants - Bernier, Virginie; Lefebvre, Nicholas; Khelifi, Mohamed; Renkema, Justin; Fournier, Valérie (Phytoprotection, 2023)
Cyclamen mite (Phytonemus pallidus Banks) can be eliminated from strawberry (Fragaria × ananassa Duchesne) planting material when transplants are subjected to a controlled atmosphere temperature treatment (CATT) at 35 °C, 50% CO2 and 10% O2 under high relative humidity for 48 h. In our previous research, CATT reduced cyclamen mite numbers by 99.9%, but its effects on plant vigour were not assessed. The objective of this study was to assess the survival, yield and growth of different strawberry cultivars (‘Albion’, ‘Murano’, ‘Seascape’) and plant types (bareroot plants, trayplants) that received CATT before planting compared to untreated control plants. CATT slightly increased the risks of plant mortality, and plant losses were greater for trayplants than for bareroot plants. CATT resulted in increased runner production for ‘Albion’ transplants but caused no effects on other cultivars. Fruit yields were either unaffected or decreased by CATT, suggesting stimulation of vegetative rather than reproductive growth. Based on these results, disinfection of strawberry transplants using CATT would be more suitable for plants destined for propagation rather than for fruit production. Our research highlights the need to develop a universal and easily adoptable treatment effective against multiple pests and pathogens to produce clean strawberry transplants.